2022
DOI: 10.26773/smj.221010
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Maximal Aerobic Capacity based on Self-Reported Physical Activity Levels among Adolescents

Abstract: Growing evidence has indicated a positive association between physical activity and cardiorespiratory fitness (i.e., maximal aerobic capacity or VO2 max). Limited evidence, however, is available among adolescents. This research aimed to predict VO2 max based on the physical activity level and estimate the discriminant capacity of the physical activity levels on the VO2 max status among adolescents. This research was a cross-sectional study in 141 adolescents (age 19±1 year old, 83% male). The VO2 max was asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…A growing body of research has suggested that regular physical activity can be an effective means of preventing and managing these chronic diseases, making it an important aspect of maintaining overall health and well-being (Anindita et al, 2019). One group that has been identified as having a high potential for physical activity is adolescents, particularly students, due to academic pressures and sedentary lifestyles (Arovah & Purnomo, 2022). The increase in physical inactivity among adolescents, particularly students, is alarming as it can negatively their physical and mental health (Shigeta et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of research has suggested that regular physical activity can be an effective means of preventing and managing these chronic diseases, making it an important aspect of maintaining overall health and well-being (Anindita et al, 2019). One group that has been identified as having a high potential for physical activity is adolescents, particularly students, due to academic pressures and sedentary lifestyles (Arovah & Purnomo, 2022). The increase in physical inactivity among adolescents, particularly students, is alarming as it can negatively their physical and mental health (Shigeta et al, 2021).…”
Section: Introductionmentioning
confidence: 99%